Odpowiedź :
Odpowiedź:
dla x = 2 i y = 3
- 5x -y = - 5 · 2 - 3 = - 10 - 3 = - 13
3x + 2y = 3 · 2 + 2 · 3 = 6 + 6 = 12
- x + y = - 2 + 3 = 1
-0,5xy = -0,5 · 2 · 3 = -1 · 3 = -3
9x + 5y = 9 · 2 + 5 · 3 = 18 + 15 = 33
7x + 4y = 7 · 2 + 4 · 3 = 14 + 12 = 26
x - y = 2 - 3 = - 1
- 2x + y = - 2 · 2 + 3 = -4 + 3 = -1
Szczegółowe wyjaśnienie:
(Mam nadzieję, że pomogłam)
Odpowiedź:
9x+5y=9*2+5*3=18+15=33
-5x-y=-10-3=7
x-y=2-3=-1
3x+2y=12
-0,5xy=-0,5*2*3=-1*3=-3
-x+y= -2+3= 1
7x+4y=14+12=26
-2x+y= -4+3= -1